Analisis ekspor Crude Palm Oil (CPO) Provinsi Jambi periode 1999-2018 - Primahesa, Tegar; Hidayat, M. Syurya; Parmadi, Parmadi (e-Journal Perdagangan Industri dan Moneter, 2022)
The purpose of this study was to analyze the development of exchange rates, CPO prices, coconut oil prices, and Jambi CPO Exports and to investigate the effect of exchange rates, CPO prices, and coconut oil prices on Jambi Province CPO Exports. The analytical methods used are descriptive analysis and quantitative analysis. The data used in this study was secondary data with Time Series data types from 1999-2018. The data sources used in this study are the Jambi provincial plantation office, central statistics agency of Jambi province, bank Indonesia and world bank. The data analysis technique used is multiple linear regression analysis. The results showed that: (1) The development of CPO exports of Jambi Province, rupiah exchange rate, CPO price, and coconut oil price tends to fluctuate every year. (2) Variable exchange rate and CPO price significantly affect CPO exports of Jambi Province. In contrast, coconut oil variables do not significantly affect CPO exports of Jambi Province.